2004
DOI: 10.1590/s1806-83242004000300017
|View full text |Cite
|
Sign up to set email alerts
|

Dentine bond strength of a composite resin polymerized with conventional light and argon laser

Abstract: ABSTRACT:The use of argon laser (488 nm) has been suggested as a new alternative for polymerizing adhesive materials. This study aimed to evaluate the tensile bond strength of a microfilled composite (A110, 3M) inserted by incremental technique (3 increments of 1 mm) and by single increment (3 mm) polymerized by argon laser for 10, 20 and 30 seconds and halogen light for 40 seconds. Eighty (8 groups of 10 teeth) freshly extracted bovine teeth were stored in a freezer in distilled water for one week. The crowns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
1
0
4
Order By: Relevance
“…7 Use of the Argon ion laser as a light-curing source is controversial. While some authors affirm that this laser is efficient and capable of polymerizing resin composites more rapidly and with better physical and mechanical properties when compared with the halogen light curing unit, 8 other authors have shown the laser action to be less efficient [9][10] due to a difference in Argon ion laser wavelength of 488 nm from 470 nm, which is the absorption peak of camphorquinone. 1 The use of LEDs to polymerize resin composites was proposed by Mills in 1995.…”
Section: Introductionmentioning
confidence: 99%
“…7 Use of the Argon ion laser as a light-curing source is controversial. While some authors affirm that this laser is efficient and capable of polymerizing resin composites more rapidly and with better physical and mechanical properties when compared with the halogen light curing unit, 8 other authors have shown the laser action to be less efficient [9][10] due to a difference in Argon ion laser wavelength of 488 nm from 470 nm, which is the absorption peak of camphorquinone. 1 The use of LEDs to polymerize resin composites was proposed by Mills in 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Diaset al 23 estudaram a força de adesão de três adesivos ao esmalte bovino através do preparo com broca diamantada, broca carbide e desgaste por lixa de papel. Também Lloret et al 24 utilizaram o laser de argônio em dentes bovinos para testes de adesividade de resinas.…”
Section: Discussionunclassified
“…Apesar da força de adesão ao esmalte bovino ser 35% mais fraca quando comparada ao esmalte humano 2 , outros estudos mostraram que os dentes humanos podem ser tranqüilamente substituídos pelos dentes bovinos em muitos tipos de pesquisa, principalmente naquelas sobre colagem, adesividade e força de tração [22][23][24][25] . Por outro lado, outro estudo mostrou que a adesividade no esmalte bovino pode ser maior que em esmalte humano 30 .…”
Section: Discussionunclassified
“…Embora existam relatos na literatura (BLANKENAU et al, 1991;MAILLET, 1999;TURBINO, 2004;DELFINO et al, 2006) de que melhores propriedades mecânicas dos compósitos são obtidas com o laser de argônio, os resultados obtidos com essa nova fonte de luz ainda são muito controversos (NAUFEL;RODE et al, 2005;TURBINO et al, 2005;TURBINO, 2007). Além disso, não há estudos avaliando a tensão de contração da resina composta ativada com laser de argônio, nem estudos relacionando esta tensão com as propriedades mecânicas da resina composta.…”
Section: Lista De Figurasunclassified
“…Como a luz halógena é absorvida, dispersa e, conseqüentemente, atenuada durante a sua passagem através da massa de resina (RUEGGEBERG; CAUGHMAN; CURTIS JR, 1994), as superfícies mais próximas à fonte de irradiação de luz polimerizam mais eficientemente que aquelas mais profundas (TURBINO, 2004;NAUFEL;RODE et al, 2005 (EICK et al, 1993;ILIE et al, 2007). Ilie et al (2007) analisaram a contração de um material compósito inovador para restaurações dentais, baseado em um monômero com uma nova formulação química, conhecido como "silorane".…”
Section: Revisão Da Literaturaunclassified